2020
DOI: 10.3126/njr.v10i2.35972
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Subpubic Angle in Radiograph

Abstract: Introduction: Subpubic angle, an important parameter used for sex determination in the pelvis, is the angle between two inferior pubic rami below the symphysis pubis. This study was carried out to determine the subpubic angle among the individuals referred for pelvic and KUB radiographs in the department of Radiology and Imaging, Tribhuvan University, Teaching Hospital.Methods: Prospective cross-sectional study was done on 120 individuals. The subpubic angle was measured by drawing two tangent lines on the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The findings of the present study are comparable with that of Kayastha P, et al (SPA of male= 104.72±10.47°, SPA of female= 137.15±11.92°), who also attempted to determine the SPA using digital pelvic radiographs in the Nepalese population as in our study. 16 On the other hand, the SPA was considerable lower in other studies; 59.05±7.11° in males and 75.60±9.81° in females in a morphometric study performed on 40 adult dry articulated pelvis 1 and 68.6±7.6° in males and 87.4±6.5° in females in a study done in reconstructed threedimensional computed tomography pelvic model in a Malaysian population. 3 Discrepancies in SPA made by our study in comparison with other studies may be due to variation in the modalities adopted in measuring SPA and different ethnic groups.…”
Section: Iscussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The findings of the present study are comparable with that of Kayastha P, et al (SPA of male= 104.72±10.47°, SPA of female= 137.15±11.92°), who also attempted to determine the SPA using digital pelvic radiographs in the Nepalese population as in our study. 16 On the other hand, the SPA was considerable lower in other studies; 59.05±7.11° in males and 75.60±9.81° in females in a morphometric study performed on 40 adult dry articulated pelvis 1 and 68.6±7.6° in males and 87.4±6.5° in females in a study done in reconstructed threedimensional computed tomography pelvic model in a Malaysian population. 3 Discrepancies in SPA made by our study in comparison with other studies may be due to variation in the modalities adopted in measuring SPA and different ethnic groups.…”
Section: Iscussionmentioning
confidence: 75%
“…SPA declines as people age. 16 Akhlaghi M, et al also noted a significant decrease in SPA with an increase in age in females. 19 However, Karakas HM, et al did not find any correlation between the SPA and age, 20 while Nwoha reported that the older individuals have lager SPA compared to the younger ones.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations